Do firms benefit from complementarity effect in R&D and what drives their R&D strategy choices? - Uwe Cantner; Ivan Savin (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
This paper analyzes whether firms conducting internal R&D and acquiring external high-tech equipment experience a complementarity effect. For German CIS data we conduct a complete set of indirect and direct complementarity tests refining the analysis by looking at various types of innovations and industries. Complementary effects are found in the indirect but not so in the direct approach. In contrast to previous literature, we find the distinct R&D strategy choices to be significant drivers of innovative activity and we identify contextual variables explaining the joint occurrence of the two strategies.
Keywords: O14; O31; O32; O33; 330; complementarity; equipment with embodied technology; innovation; internal R&D; Pavitts sectoral taxonomy